Projetos de vida profissional de estudantes universitários : um estudo na área da ética e da moralidade - Abreu, Elzenita Falcão (2012)
This study research consists of analyzing, from the perspective of morality and ethics, the way of thinking of college students in the health field about their life projects and the influence of their teachers in these projects. We tried to know the projects and analyze them based on La Taille (2006a) contributions. The investigation was done with 51 students, men and women, of Nursing, Medicine and Psychology courses, of the first and last periods of the courses, of Universidade Federal do Vale do São Francisco – UNIVASF. We conduct individual interviews, according to the clinical method of Piaget (1926/2005, 1932/1994). Considering the most frequent answers and explanations, concerning the project of professional life, we verify that: (1) the project professional life that students refer to is the "postgraduate" and justified this for "motivation and/or interest"; (2) all participants have the belief that their projects will be made and emphasized the "determination" as a reason; (3) the strategy on how the projects will be carried out is "studying", followed by the justification "way of achieving the goals"; (4) “Petrolina, Juazeiro” and neighboring cities are the places where they intend to carry out their projects, under the argument of being the "best alternative"; (5) the positive and negative things of education are, respectively, the "teachers" and "structure of the university"; (6) the majority of respondents believes that teachers have influence on their projects for "guidance and/or encouragement in their choice of paths" and (7) the manners of teachers use to influence are "the way they relate with students" and "demonstration of knowledge of the area." Faced with the answers and arguments, we find that few data (10.25%) express moral content, or not pointing to the ethical perspective. Thus, we can’t say that the future professionals based on the aspects mentioned moral and ethical principles as meaning that we treat in this research. Finally, we expect the data instigate work of intervention that lead to reflections on the principles that should guide professional practice and encourage further research in the area of morality.